SGLT2 INHIBITORS BEYOND DIABETES A RETROSPECTIVE AUDIT OF PRESCRIBING PATTERNS IN PATIENTS WITH HEART FAILURE WITH PRESERVED EJECTION FRACTION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Heart failure with preserved ejection fraction (HFpEF) constitutes a substantial and increasing proportion of heart failure cases worldwide, with historically limited evidence-based therapeutic options. Sodium–glucose co-transporter 2 (SGLT2) inhibitors, initially developed for the management of type 2 diabetes mellitus, have demonstrated significant cardiovascular benefits, including reductions in heart failure hospitalizations and improvement in functional outcomes, irrespective of glycemic status. This retrospective audit aimed to evaluate prescribing patterns of SGLT2 inhibitors in patients with HFpEF, with particular emphasis on their utilization beyond diabetes.